Calculation of melt pond albedos on Arctic sea ice - Makshtas , Alexander P.; Podgorny , Igor A. (Polar Research, 1996)
An analytical approximation of spectral albedo is derived for a melt pond with a Lambertian bottom assuming that Rayleigh scattering in the water is small compared to absorption. A Monte Carlo method is used to verify that scattering can he ignored in the water. This enables us to calculate pond albedos in the 400–700 nm wavelength hand using the analytical approximation. Model calculations and observations indicate that a step-decrease in albedo is likely t o occur when a melt pond initially forms, and melt pond albedos in the visible depend more on the structural and optical properties of the bottom than on the depth of the pond.